Economic Potential of Switchgrass as a Biofuel Crop in Florida - Zane R. Helsel; Jose Alvarez (EDIS)
Switchgrass has been recognized by the United States Department of Energy as a potentially important source of ethanol. This publication evaluates the economic potential of producing switchgrass as a perennial bioenergy crop in Florida. In South Florida, two cuts of "hay" for biofuel are possible, whereas in North Florida, one cut would normally be taken after frost in late fall. These two harvest systems are evaluated and compared, and cost estimates are provided. This 7-page fact sheet was written by Zane R. Helsel and José Álvarez, and published by the UF Department of Food and Resource Economics, December 2011.